Vue. js Quick Start Guide : Learn How to Build Amazing and Complex Reactive Web Applications Easily Using Vue. js. - Imsirovic, Ajdin (Packt Publishing Ltd, 2018)
Vue.js is the latest trending frontend framework. Simplicity, reactivity, and ﬂexibility are some of the key benefits that Vue offers to developers. This book will help you learn everything you need to know to build stunning reactive web apps with Vue.js 2 quickly and easily.